TINGGINYA BIAYA TRANSPORTASI DARAT DALAM MENUNJANG DISTRIBUSI BARANG KEBUTUHAN POKOK MASYARAKAT PINOGU KABUPATEN BONE BOLANGO - Alkatiri, Ramlah; Rasadingi, Hapsa (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2024)
This study aims to determine the high cost of land transportation in supporting the distribution of basic necessities for the Pinogu community, Bone Bolango Regency. This study uses a qualitative approach using interview instruments to various randomly selected information. The results showed that the only land transportation (ojek) to Pinogu District has a high strategic cost in supporting the distribution of basic necessities of the community because it is a means of transportation that is able to encourage the movement of goods and people from and to Pinogu. Especially in the distribution of basic necessities of the Pinogu community.